Fraud examiners manual volume I - Association of Certified Fraud Examiners; Association of Certified Fraud Examiners (Austin, Texas : Association of Certified Fraud Examiners, 2015)
Fraud Examiners Manual represents a common knowledge in the fraud examination field and describes thousands of fraud schemes and the techniques that can be used to prevent and detect them.
Financial transactions and fraud schemes; law; investigation methods; fraud prevention and deterrence.
rua 24/06/15
Loans
Keywords: Fraud detection; Criminal Investigation